2016
DOI: 10.1186/s12906-016-1270-2
|View full text |Cite
|
Sign up to set email alerts
|

Quality assurance of the university medical education, hospital services and traditional pharmaceutical products of the Bhutanese So-wa-rig-pa health care system

Abstract: BackgroundThe Bhutanese So-wa-rig-pa medicine (BSM) was integrated with the allopathic (modern) health care system in 1967. Ever since the health care integration policy was implemented, the BSM has gone through many phases of quality improvement and changes including the establishment of one university-based institute, 58 hospitals and Basic Health Units (BHU)-based health care services, and one traditional medicine factory. The BSM provides primary health care services to more than 20–30 % of patients who vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…There is still a dearth of literature resulting from the last decade’s investigations addressing procedures to be adopted for quality assurance, authentication, and standardization of crude plant products, despite ongoing thorough and mechanism-oriented evaluations of medicinal plants from the Saharan region’s flora. The formulation of the finished product, extraction techniques, and proper raw material management may all contribute to achieving the desired consistency [ 16 , 102 ]. In fact, it has been acknowledged that one of the main obstacles to the formation of a modern phytomedicine business in the Saharan region is the lack of proper validation of traditional knowledge, as well as technological needs and quality control standards.…”
Section: General Debatementioning
confidence: 99%
“…There is still a dearth of literature resulting from the last decade’s investigations addressing procedures to be adopted for quality assurance, authentication, and standardization of crude plant products, despite ongoing thorough and mechanism-oriented evaluations of medicinal plants from the Saharan region’s flora. The formulation of the finished product, extraction techniques, and proper raw material management may all contribute to achieving the desired consistency [ 16 , 102 ]. In fact, it has been acknowledged that one of the main obstacles to the formation of a modern phytomedicine business in the Saharan region is the lack of proper validation of traditional knowledge, as well as technological needs and quality control standards.…”
Section: General Debatementioning
confidence: 99%
“…5 Missing � 49. 6 Missing � 33. e superscripts represent the number of missing data for each variable.…”
Section: Attitude Parametersmentioning
confidence: 99%
“…e Traditional Medicine Units (TMUs) are colocated with allopathic hospitals and offer their age-old treatment recipes and healing procedures [4,5]. BTM drug recipe not only follows its traditional methods of identification, collection, and manufacturing of herbal plants but also follows modern methods of quality assurance in drug manufacturing, storage, and distribution [6]. Surgical therapies include bloodletting, oil and heat moxibustion, cupping, and the indigenous gold needle therapy that generate sharps and infectious wastes.…”
Section: Introductionmentioning
confidence: 99%
“…Herbal bath therapy is an integral part of traditional BSM health care services. We have previously described how QSE of BSM is managed and regulated under the settings of university medical education, hospital services, and pharmaceutical production processes [78]. We found that NTMH developed numerous standard guidelines and reference materials through a series of consultative workshops to provide BSM treatments with the same quality, safety, and effectiveness.…”
Section: Quality Safety and Efficacy Of Medical Hydrology In Bhutan 421 Herbal Bath Therapymentioning
confidence: 99%
“…We found that NTMH developed numerous standard guidelines and reference materials through a series of consultative workshops to provide BSM treatments with the same quality, safety, and effectiveness. These guidelines are (i) diseases codes and classification system for correctly diagnosing the diseases; (ii) standard treatment guidelines for traditional medicine; (iii) national traditional medicine professional service standards; (iv) therapy guidelines (including herbal bath therapy) for traditional medicine practitioners; (v) standard operating procedures for traditional medicine services; and (vi) guidelines for detecting, reporting, and managing adverse drug reactions [78][79][80][81]. The traditional physicians and clinical assistants are trained on following, operating, and using these guidelines while providing the traditional medical health care services.…”
Section: Quality Safety and Efficacy Of Medical Hydrology In Bhutan 421 Herbal Bath Therapymentioning
confidence: 99%